Architect of Nothingness - Ecem Sarıçayır (Footprint)
Architect Frank van Klingeren was most active during the 1960s and 1970s in the Netherlands. In response to the social and urban challenges of the time, Van Klingeren developed various experimental architectural forms and concepts. This essay discusses his comparatively well-known community centres De Meerpaal and Het Karregat by focusing on his commitment to unfinished architecture, open plan through wall-less designs, and his insistent attempt at creating social encounters through these spatial principles. To provide historical contextualisation of these architectural principles I engage with a theoretical framework developed by Esra Akcan which provides the first full-fledged conceptualisation of open architecture. I look at archival materials such as Van Klingeren’s poems, essays, and interviews as well as the designs of his community centres and their reception in national and international journals and newspapers. In addition to extending our knowledge of Van Klingeren’s seldom studied architectural practice, this essay aims to contribute to the concept of openness in architectural studies with the case of Van Klingeren’s spatial practice.